2019
DOI: 10.1051/e3sconf/20199702005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminium Powder on Light-weight Aerated Concrete Properties

Abstract: Light-weight aerated concrete (LAC) is produced by making LAC involves the addition of a gas-forming admixture like aluminium powder (AP) to a wet mortar mixture. In concrete during curing, AP will react with the calcium hydroxide in the mixture to form hydrogen. The amount of gas-forming is dependent on the mechanical properties requirements. The aim of the current work was to investigate the properties of aerated concrete (AC) containing 30% fly ash and various AP content, including dry density, porosity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…In recent years, there has been a steady trend towards increased demand for autoclaved aerated concrete products, which are characterised by low thermal conductivity with sufficient density and strength due to the presence of a significant number of artificially created pores. The main problem of autoclaved aerated concrete technology is the multi-component composition and instability of the porization process which can result in lowering of the compressive strength [14][15][16][18][19][20][21]. The analysis of literature sources showed that to obtain light and ultra-light concrete, two ways of obtaining cells are mainly used: the introduction of gas formers into the concrete mass (aluminium powder or aluminium paste) or the foam formers mainly based on an organic compounds.…”
Section: Autoclaved Aerated Concrete Technology Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been a steady trend towards increased demand for autoclaved aerated concrete products, which are characterised by low thermal conductivity with sufficient density and strength due to the presence of a significant number of artificially created pores. The main problem of autoclaved aerated concrete technology is the multi-component composition and instability of the porization process which can result in lowering of the compressive strength [14][15][16][18][19][20][21]. The analysis of literature sources showed that to obtain light and ultra-light concrete, two ways of obtaining cells are mainly used: the introduction of gas formers into the concrete mass (aluminium powder or aluminium paste) or the foam formers mainly based on an organic compounds.…”
Section: Autoclaved Aerated Concrete Technology Researchmentioning
confidence: 99%
“…The influence of aluminium powder dosage on selected properties of aerated concrete containing 30% of fly ash was researched in [20]. Aluminium powder was introduced into the composition of foamed concrete in the amount from 0.25 to 1.00% of cement mass.…”
Section: Autoclaved Aerated Concrete Technology Researchmentioning
confidence: 99%
“…They scatter among and separate the cement particles because of their distribution of smaller-sized particles. By utilising fibers and aluminium powder in reaction with cement, a novel concrete combination that produces durable concrete will be produced [13][14][15][16]. From the explanation above, it is clear that polypropylene fibers and aluminium powder are becoming more popular in concrete building and may eventually take the place of traditional concrete.…”
Section: Need For Addition Of Polypropylene Fibers and Aluminium Powd...mentioning
confidence: 99%
“…The search for an aerating agent [5][6][7] that avoids all these issues is therefore of high relevance for the producers who, moreover, could also reduce the safety-related costs.…”
Section: Bio Innovation In the Processmentioning
confidence: 99%